Improving the care of HIV-infected and -affected children during the implementation phase of the large-scale antiretroviral therapy programme in South Africa - Feucht, Ute Dagmar (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2023.